SOCIAL-PSYCHOLOGICAL CHARACTERISTICS OF PROVIDING PSYCHOLOGICAL HELP TO PERSONS IN DANGEROUS AND EMERGENCY SITUATIONS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The article provides information about the types of extreme situations of a person, analyzed them from a psychological point of view, and highlighted the socio-psychological features of providing psychological assistance to a person in such a situation.